Human Rights Violations and International Legal Responses - Ribut Harwanto, Edi (Journal of Law and Social Politics, 2025)
Background: Human rights violations remain a persistent global challenge, particularly in contexts of armed conflict, authoritarian rule, and socio-political instability. Although international legal frameworks exist to prevent and punish such abuses, accountability and effective enforcement remain problematic. Objective: This study aims to analyze contemporary human rights violations and evaluate the effectiveness of international legal mechanisms in addressing accountability and justice. Methods: A qualitative approach is employed through doctrinal legal analysis and case studies. The research examines key international legal instruments, including the Universal Declaration of Human Rights, the Geneva Conventions, and the Rome Statute, supported by reports from the United Nations, the International Criminal Court (ICC), and regional human rights bodies. Case studies from Ukraine, Myanmar, Ethiopia, and Venezuela are analyzed. Results: The findings show that international legal frameworks provide important normative and institutional mechanisms to address war crimes, crimes against humanity, and genocide. However, enforcement remains inconsistent due to political interests, limited jurisdiction, and lack of state cooperation. Case studies reveal both the potential and limitations of international legal interventions. Conclusion: The study concludes that strengthening international legal responses requires enhanced international cooperation, greater judicial independence, and more effective enforcement and sanction mechanisms to ensure global accountability in human rights protection.